Sinterabilidade, desenvolvimento microestrutural e caracterização elétrica do BaCe0,9Y0,1O3-ẟ nanométrico obtido por mistura de óxidos - Ramos, Kethlinn (2018)
In this thesis, we investigated the microstructural development of BaCe0,9Y0,1O3-ẟ starting from aggregate-free submicrometric and nanometric powders. The differential of these powders is that synthesis occurred via solid-state reaction, compared to powders commonly used in the literature in the same size range. Nanometric particles were obtained by alternating steps of calcination with steps of grinding using isopropyl alcohol as dispersion media in a vibratory mill, and varying grinding time and load (weight ratio of grinding media/powder), with care to particle deflocculation, as well as keeping the grinding jars filled at only 50% of total capacity. The sinterability of compacts was surprisingly high, compared to literature reports, so that sintered samples with density higher than 95% of theoretical density were obtained at only 1200°C with dwell time of 10 hours. Literature shows that this degree of sintering is only achieved with the use of sintering aids. Systematic monitoring of microstructural development of the green compacts made with the different powders obtained in this thesis allowed the detection of a liquid phase appearing around 1200°C, which has not yet been reported in the literature. In green compacts with aggregates, the liquid phase was consumed in the densification of these defects so that macroporosity would remain even after sintering at 1600°C. In aggregate-free green compacts, the liquid phase aided to achieve high and homogeneous densification, mostly around the initial temperature of its formation. However, even after achieving high densification at low temperatures, higher ones are required in order to develop the microstructure in ways to reach adequate protonic electrical conductivity. The microstructure developed by powders obtained by grinding with 20:1 ratio (grinding media/powder) for 24h and sintered at 1600°C showed a proton conductivity of 2x10-2S/cm at 600°C which is in agreement with the best results in the literature.